The Business Ethics and its Role in Achieving the Performance Efficiency "Analytical Study of the Views of a Sample to the Staff in the Presidency of University of Zakho " - Ali, Nizar M.; Ismail, Jagar M.; Haji, Avan Y. (Humanities Journal of University of Zakho, 2017)
The research aims to identify the business ethics and their role in achieving the performance efficiency. Research descriptive and analytical approach were used. To identify the variables a tool has designed For data collection, consisting of (30) paragraph and its representing the paragraphs of business ethics and the performance efficiency. The outcomes of Questionnaire were analyzed and distributed to the administration staff at the presidency of Zakho University which it were (44) statistical forms and displayed by (SPSS) using statistical forms average, standard deviations, and the relationship between the Line and influence. Descriptive analysis of the variables business ethics shown that the degree of overall variable agreement reached (62.28%). also the degree of overall variable agreement of performance efficiency reached (46.67%). Based on the research test and its hypo thesis research found there were a significant correlation between business ethics and efficient performance at all level. The existence of moral effect were found in business ethics in the performance efficiency at all level. Based on the conclusion a subjections has set, the most important subject to everyone wither they are academics or employs in the education institution. Research sample shad work to gather to determine the works ethics and to give more attention in how to continue to apply the moral control and its elements, also to focus on compliance with regulation as model for the application of work ethic because of its role in enhancing the performance of the institution operations. All the powers would assist them must be given to wards a achieving the goals also in order to address the problem of the low level of performance. And develop their abilities and improve their performance also participating in scientific conferences, seminars and training programs specialized in quality of performance.